2007
DOI: 10.1140/epje/e2007-00029-6
|View full text |Cite
|
Sign up to set email alerts
|

On coupling between the orientation and the shape of a vesicle under a shear flow

Abstract: A simple 2D model of deformable vesicles tumbling in a shear under flow is introduced in order to account for the main qualitative features observed experimentally as shear rates are increased. The simplicity of the model allows for a full analytical tractability while retaining the essential physical ingredients. The model reveals that the main axes of the vesicle undergo oscillations which are coupled to the vesicle orientation in the flow. The model reproduces and sheds light on the main novel features repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Such a fluid-to-solid transition has been observed for other soft-matter particulates, e.g., capsules [14][15][16][17][18][19] and vesicles [20][21][22][23][24][25][26][27][28][29][30][31], which are membrane-bound liquid drops and hence structurally similar to erythrocytes. The mechanical properties of the membranes are, however, different in the three cases; e.g., the membrane of erythrocytes * Corresponding author: pbagchi@jove.rutgers.edu is known to exhibit a resistance against shear deformation, area dilatation, and bending, whereas a vesicle membrane is incompressible, and it exhibits a bending resistance.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Such a fluid-to-solid transition has been observed for other soft-matter particulates, e.g., capsules [14][15][16][17][18][19] and vesicles [20][21][22][23][24][25][26][27][28][29][30][31], which are membrane-bound liquid drops and hence structurally similar to erythrocytes. The mechanical properties of the membranes are, however, different in the three cases; e.g., the membrane of erythrocytes * Corresponding author: pbagchi@jove.rutgers.edu is known to exhibit a resistance against shear deformation, area dilatation, and bending, whereas a vesicle membrane is incompressible, and it exhibits a bending resistance.…”
Section: Introductionmentioning
confidence: 57%
“…The experiments by Fischer et al [6], Tran-Son-Tay [8], and Fischer [10] did not consider the swinging erythrocytes. Very importantly, several recent studies have shown that a significant shape oscillation (vacillating breathing or trembling motion) may coexist during the swinging motion [22][23][24][25][26][27][28][29][30][31]. Hence, the shape and angular oscillations are highly coupled.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have reported that VB exists for intermediate λ or capillary number [33]. Another measurable effect of increasing the capillary number on tumbling vesicles is a decrease of the tumbling frequency when approaching the transition to VB [12,40]. There is a consensus from theoretical studies that the phase diagram of the three regime (TT, VB and TB) has the shape shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Considerable knowledge about the individual dynamics of vesicles in different types of flow has been accumulated thanks to the intensive theoretical [23][24][25][26][27][29][30][31][32]74] and experimental [33][34][35][36][37][38][39]75] investigations performed so far. Recently, an important progress in this direction was made.…”
Section: Dynamics Of Vesicles In Unconfined Shear Flows: Overview Of mentioning
confidence: 99%
“…The theoretical background of the problem [23][24][25][26][27][28][29][30][31][32] and the experimental work performed so far [33][34][35][36][37][38][39] are reviewed and discussed. The theoretical background of the problem [23][24][25][26][27][28][29][30][31][32] and the experimental work performed so far [33][34][35][36][37][38][39] are reviewed and discussed.…”
mentioning
confidence: 99%